2001
DOI: 10.1176/appi.ps.52.6.805
|View full text |Cite
|
Sign up to set email alerts
|

Using Drug Claims Data to Assess the Relationship of Medication Adherence With Hospitalization and Costs

Abstract: The availability of drug claims data and the ability to use them in predictive analyses make them a potentially useful data source in studies of medication adherence among persons with severe mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
192
2
16

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(219 citation statements)
references
References 24 publications
9
192
2
16
Order By: Relevance
“…Studies consistently showed that nonadherence was significantly associated with poorer outcomes, including greater risk of hospitalization [Ahn et al 2008;Eaddy et al 2005;Gilmer et al 2004;Law et al 2008;Morken et al 2008;Svarstad et al 2001;Valenstein et al 2002;Weiden et al 2004a], greater use of emergency services , longer length of hospital stay Valenstein et al 2002] and greater risk of suicide [Leucht and Heres, 2006;Llorca, 2008]. The consequences to society included having to deal with the consequences of violence , substance abuse and criminal behaviour .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies consistently showed that nonadherence was significantly associated with poorer outcomes, including greater risk of hospitalization [Ahn et al 2008;Eaddy et al 2005;Gilmer et al 2004;Law et al 2008;Morken et al 2008;Svarstad et al 2001;Valenstein et al 2002;Weiden et al 2004a], greater use of emergency services , longer length of hospital stay Valenstein et al 2002] and greater risk of suicide [Leucht and Heres, 2006;Llorca, 2008]. The consequences to society included having to deal with the consequences of violence , substance abuse and criminal behaviour .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was difficult to make comparisons, and it was not feasible to pool the quantitative results on the relationship between nonadherence and increased risk of hospitalization. However, regardless of the heterogeneity in adherence measures used, all studies consistently showed a link between lower adherence rates and higher hospitalization risk [Ahn et al 2008;Eaddy et al 2005;Gilmer et al 2004;Karve et al 2009;Knapp et al 2004;Laan et al 2010;Law et al 2008;Morken et al 2008;Svarstad et al 2001].…”
Section: Consequences To Patientsmentioning
confidence: 99%
“…Non-adherence with prescribed therapeutics remains the highest predictor of patient relapse and rehospitalization (Ayuso-Gutierrez and del Rio Vega 1997; Harris et al 2002;Lieberman et al 2005;Olfson et al 2000;Svarstad et al 2001). Up to 55% of individuals with schizophrenia have significant difficulties adhering to treatment (Corriss et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Up to 55% of individuals with schizophrenia have significant difficulties adhering to treatment (Corriss et al 1999). Non-adherent patients are twice as likely to undergo rehospitalization from relapse (Svarstad et al 2001), resulting in a poor quality of life. A Medicaid study found that only 11.6% of treated patients achieved 1 year of uninterrupted antipsychotic medication therapy (McCombs et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although symptoms remain a concern for some on these medications (Judd et al, 2003), evidence has accrued to suggest that mood-stabilizing medications substantially diminish symptoms as well as hospitalization rates (cf., Smith, Cornelius, Warnock, Bell, & Young, 2007). Despite this, estimates suggest that one-third to one-half of patients with bipolar disorder discontinue medication treatment over time (Basco & Rush, 1995;Svarstad, Shireman, & Sweeney, 2001). Lack of adherence to mood stabilizers has been shown to contribute to poorer course of disorder and more frequent hospitalization (Scott & Pope, 2002).…”
mentioning
confidence: 99%